Hot Tea Consumption and Esophageal Cancer Risk: A Meta-Analysis of Observational Studies - Luo, Hui; Ge, Hong (Frontiers in Nutrition, 2022)
Objective: Many laboratory studies have shown that tea consumption protected against the development of esophageal cancer (EC). However, in epidemiological studies, inconsistent or even contradictory results were frequently observed, especially when drinking tea at higher temperatures. Methods: We conducted a meta-analysis on the basis of published observational studies to explore whether hot tea consumption was a risk factor of EC. Relevant studies were searched in PubMed, Embase and Web of science up to October, 13th, 2021, and we also manually retrieved the literatures in the included studies and recent reviews. Results: A total of 23 eligible reports were identified, including 5,050 cases and 10,609 controls, and a meta-analysis with Comprehensive Meta-Analysis (CMA) software (version 2.0) was conducted. A statistically significant increased EC risk was observed when drinking tea at higher temperature (odds ratios (OR) = 1.79, 95% CI: 1.48-2.15, p=0.00). This increased risk was also found in the majority of subgroups, except in esophageal adenocarcinoma (EAC), European and Australian populations. Conclusions: This meta-analysis showed that people who drank hot tea had a significantly increased risk of Esophageal squamous cell carcinoma (ESCC), but no significant association for EAC.